Antibacterial Effect of All-in-one Self-etch Adhesives on Enterococcus faecalis - Mohammad Esmaeel Ebrahimi Chaharom; Amir Ahmad Ajami; Mehdi Abed Kahnamouei; Elmira Jafari Navimipour; Pardis Tehranchi; Vahid Zand; Mohammad Reza Sadeghi; Aydin Sohrabi (Tabriz University of Medical Sciences, 2014)
Background and aims. The aim of this study was to evaluate the antibacterial activity of one-step self-etch adhesives on Enterococcus faecalis on days 1, 7 and 14 with the use of modified direct contact test. Materials and methods. The modified directcontact test was used to evaluate the antibacterial effect of Adper Easy One, Bond Force, Clearfil S3 Bond, Futurabond M, G-Bond, iBond and OptiBond All-in-one adhesives on Enterococcus faecalisafter aging the samples in phosphate-buffered saline for one, seven and fourteen days. Data were analyzed using one-way ANOVA and post hoc Tukey tests. Aging effect of each adhesive was evaluated by paired-sample test. In this study, P<0.05 was considered significant. Results. All the tested adhesives exhibited antibacterial activity after one day and had significant differences with the posi-tive control group (P<0.05). After one week, OptiBond All-in-one, iBond and Futurabond M exhibited significant differ-ences in bacterial growth from other groups (P<0.05). There were no significant differences between the groups in two weeks (P>0.05). Conclusion. iBond exhibited the highest antibacterial effect on E. faecalis after one week. Futurabond and OptiBond All-in-one exhibited antibacterial effects against E. faecalis for one week.